(untitled) (Research, Society and Development, 2020)
Autism can be defined as a persistent deficit in communication and social interaction in multiple contexts, in addition to restricted and repetitive patterns of behaviors, interests, and activities. For this purpose, the general objective is to evaluate the scientific production on the benefits of early intervention in the treatment of children with ASD. This is an integrative literature review with the guiding question: "What are the benefits of using early intervention in children with Autism Spectrum Disorder? using the PICO strategy, using the descriptors and keywords, the databases Bireme, CINAHL and PubMed were consulted. Thirteen studies were included in this review. The studies focused on the efficacy of early interventions in the development of skills and symptom relief resulting from the disorder and the importance of parents / caregivers in the application of interventions. As for the benefits, we emphasized the increase of learning capacity, socialization, language skills, as well as the reduction of stress and better coping strategies by the parents. It is concluded that early intervention provides clinical and educational benefits, each intervention should stimulate a certain area affected by ASD, increasing this stimulation in the course of the child’s progress in each skill, and it is very important to achieve significant results in time, the frequency and intensity of interventions.